Shades of ṣulḥ : the rhetorics of Arab-Islamic reconciliation - Diab, Rasha (Pittsburgh series in composition, literacy, and culture., 2016)
"Sulh is a centuries-old Arab-Islamic peacemaking practice. Rasha Diab explores the possibilities and limits of the rhetoric of sulh as it is used to resolve interpersonal, communal, and (inter)national conflicts--with a case illustrating each of these domains. The cases range from medieval to contemporary times and are analyzed using both rhetorical and critical discourse analyses"--